Self-assessed preparedness of final-year dental students and dental interns in Poland: a multi-institutional study - Jakub Jankowski; Stanisław Krokosz; Sara Zięba; Dominika Komandera; Barbara Kochańska; Jakub Fiegler-Rudol; Anna Zawilska; Ryszard Feret; Katarzyna Szczeklik; Katarzyna Gliwa; Monika Sitarz; Norbert Soboń; et al. (BMC Medical Education)
Abstract Background Dental education requires the mastery of theoretical knowledge, practical skills and social competence to provide patients with appropriate medical care. Our cross-sectional study aimed to assess the self-reported preparedness of final-year dental students and dental interns at all ten dental universities in Poland. Methods We used the validated questionnaire “Dental Undergraduates Preparedness Assessment Scale” (DU-PAS), which consisted of 50 items divided into two sections: section A (24 items associated with clinical manual skills) and section B (26 items related to cognitive and behavioural features). The online survey was addressed to final-year dental students and dental interns (recent graduates) from all Polish universities. Depending on the academic centre, the Google link was disseminated via year groups in social media and/or emails. Results In our survey, 1281 respondents participated, including 739 students and 542 interns. The overall response rate was 71.6%. Most participants were females (75.1%). For most evaluated aspects, the increase in their mastery was significant for interns compared to students. Most interviewees declared independence in collecting a complete medical history and conducting a dental examination, as well as effective removal of caries and conservative reconstruction of teeth with aesthetic materials. However, they also most often had no experience in undertaking bitewing radiographs and providing prosthetic crowns. Students and interns did not significantly differ in their confidence in the application of evidence-based dentistry and interpretation of research findings for clinical practice, as well as their approach to treating children and the inappropriate behaviour of their colleagues. On the other hand, both groups assessed their preparedness to refer patients with suspected oral cancers the worst. Moreover, significant differences were observed in DU-PAS scores regarding gender and education stage. Males and interns scored significantly higher self-esteem overall, as well as separately in manual skills and social competencies. Conclusions Our study provides the first detailed evaluation of final-year dental students and interns in Poland, highlighting areas for improvement and guiding educational reforms to enhance future dentists’ independence. Despite some areas needing significant changes in the academic approach, a considerable proportion of assessed procedures demonstrated satisfactory outcomes.